Partial least square path analysis of knowledge, attitude,and practice regarding dengue - Ajibola, Lamidi-Sarumoh Alaba (Tehran University of Medical Sciences, Tehran, Iran, 2019)
Introduction: Knowledge, attitude and practices regarding dengue are latent variables which are substantiated through manifest variables. The manifest variables that form the indicative construct of knowledge, attitude and practice can be factored into sub-constructs such that the impact of each indicative variable can be verified. Method: Evaluation of the sub-constructs of knowledge, attitude and practices regarding dengue using a Partial least square path models with R programming language. Result: The measurement model revealed the sub-constructs that are negatively affecting the latent variables and the ones that are having low impact. Conclusion: This analysis gives the possibility of observing the exact knowledge, attitude and practices regarding dengue that are inadequate among respondents. The result from this methodological approach can be used as an aid for the community health programs and campaigns on how to enlighten the populace of interest on the required awareness about dengue, attitude towards dengue and the preventive practices that are deficient among them.